INKT cells with high PLZF expression are recruited into the lung via CCL21‐CCR7 signaling to facilitate the development of asthma tolerance in mice. Issue 2 (3rd September 2020) - Feng, Xintong; Zhao, Caiqi; Li, Ling; Feng, Jingjing; He, Wei; Shi, Tianyun; Li, Na; Jie, Zhijun; Su, Xiao
Abstract: Establishment of immune tolerance is crucial to protect humans against asthma. Promyelocytic leukemia zinc finger (PLZF) is an emerging suppressor of inflammatory responses. CCL21‐CCR7 signaling mediates tolerance development. However, whether PLZF and CCL21‐CCR7 are required for the development of asthma tolerance is unknown. Here, we found that Zbtb16 (coding PLZF) and Ccl21 were upregulated in OVA‐induced asthma tolerance (OT) lungs by RNA‐seq. PLZF physically interacted with GATA3 and its expression was higher in GATA3 + Th2 cells and ILC2s in OT lungs. Zbtb16 ‐knockdown in lymphocytes promoted the differentiation of CD3e + CD4 + T cells, particularly those producing IL‐4 and IL‐5. Moreover, iNKT cells with high expression of PLZF were recruited into the lungs via draining lymph nodes during tolerance. Blockade of CCL21‐CCR7 signaling in OT mice decreased the PLZF +  cell population, abolished CCR7‐induced PLZF + iNKT recruitment to the lungs, enhanced Th2responses and exacerbated lung pathology. In OT mice, respiratory syncytial virus (RSV) infection impeded PLZF +  cell and CCR7 + PLZF + iNKT cellrecruitment to the lungs and increased airway resistance. Collectively, these results indicate that PLZF could interact with GATA3 and restrain differentiation of IL‐4‐ and IL‐5‐producing T cells, iNKT cells with high PLZF expression are recruited to the lungs via CCL21‐CCR7 signaling to facilitate the development of asthma tolerance. Abstract : iNKT cells with high PLZF expression are recruited into the lung via CCL21‐CCR7 signaling to facilitate the development of asthma tolerance. PLZF physically interacts with GATA3 and restrains secretion of type 2 cytokines in T cells. RSV infection and CCL21‐blockade impair asthma tolerance by inhibiting PLZF expression and reducing recruitment of iNKT cells to the lung.